The Understanding level of Bay’ tawarruq among Muamalat students in UiTM Puncak Alam / Aiman Izzat Ghazali. - Ghazali, Aiman Izzat (2019)
This study is to know the level of understanding of tawarruq among students of the 5th semester of the diploma Muamalat Academic Contemporary Islamic Study (ACIS) UiTM Puncak Alam. This study only for the 5 semester students. The total number of students involved is 110 people(population). The method used qualitative to achieve first objective. This study also uses quantitative through the circulation of the questionnaire set among students in the semester 5. The result showed that the Muamalat students Acis, in UiTM Puncak Alam know about the tawarruq and have learn it at the class.